The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/aja.2008.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of erectile function after urethral reconstruction: a prospective study

Abstract: We conducted a prospective study of erectile dysfunction (ED) after urethral reconstructive surgery, using the 5-item International Index of Erectile Function (IIEF-5), the Sexual Life Quality Questionnaire (SLQQ) and the Quality of Life Questionnaire (QoLQ). Between January 2003 and July 2007, 125 male patients with urethral strictures underwent urethroplasty, and pre-and post-surgery erectile function was assessed using these three questionnaires. A formula to predict the probability of ED after urethroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 16 publications
2
42
1
1
Order By: Relevance
“…The pelvic trauma itself can damage the cavernosal nerves and/or to the blood supply of the corpora cavernosa (branches of the A.pudenda interna) (20). The difficult dissection at the membranous urethra during posterior urethroplasty can further damage the neurovascular structures related to the corpora cavernosa (18), although others have observed spontaneous recovery of erectile function after posterior urethroplasty (21,22).…”
Section: Iief-5mentioning
confidence: 99%
“…The pelvic trauma itself can damage the cavernosal nerves and/or to the blood supply of the corpora cavernosa (branches of the A.pudenda interna) (20). The difficult dissection at the membranous urethra during posterior urethroplasty can further damage the neurovascular structures related to the corpora cavernosa (18), although others have observed spontaneous recovery of erectile function after posterior urethroplasty (21,22).…”
Section: Iief-5mentioning
confidence: 99%
“…Baseline and post-operative IIEF-5 scores in both anterior and posterior urethroplasty have been studied. There was significant decrease in IIEF-5 scores at 3 months after posterior urethroplasty (17.05 vs. 9.37, p < 0.05), which was not observed in anterior urethroplasty (Xie et al, 2009). However, improvement of erectile function occurred at 6 months after posterior urethroplasty, especially in younger patients (<40 years) (Xie et al, 2009).…”
Section: Posterior Urethroplastymentioning
confidence: 79%
“…There was significant decrease in IIEF-5 scores at 3 months after posterior urethroplasty (17.05 vs. 9.37, p < 0.05), which was not observed in anterior urethroplasty (Xie et al, 2009). However, improvement of erectile function occurred at 6 months after posterior urethroplasty, especially in younger patients (<40 years) (Xie et al, 2009). Another study reported 40% of patients suffered from ED after pelvic fracture with a posterior urethral injury.…”
Section: Posterior Urethroplastymentioning
confidence: 89%
“…If the anastomotic urethroplasty is possible it is the procedure of choice having a success rate of approximately 90% at the intermediate follow-up [52,53]. In the patients with a 2-5 cm stricture undergoing an anastomotic procedure the risk erectile dysfunction is increased [54]. A prospective study of erectile function posturethroplasty showed anastomotic procedure in the bulbar urethra resulted in a significant impairment of erectile function initially which improved in the majority of cases.…”
Section: Open Surgical Techniquesmentioning
confidence: 99%